\[\boxed{\text{1164\ (1164).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 17^{3} + 17^{2} - 17 =\]
\[= 17^{2} \cdot (17 + 1) - 17 =\]
\[= 17^{2} \cdot 18 - 17 =\]
\[= 17 \cdot (17 \cdot 18 - 1) = 17 \cdot 305 =\]
\[= 61 \cdot 17 \cdot 5 - делится\ на\ 61.\]
\[2)\ 25^{4} - 125^{2} = \left( 5^{2} \right)^{4} - \left( 5^{3} \right)^{2} =\]
\[= 5^{8} - 5^{6} = 5^{6} \cdot \left( 5^{2} - 1 \right) =\]
\[= 5^{6} \cdot 24 = 5 \cdot 8 \cdot 5^{5} \cdot 3 =\]
\[= 40 \cdot 5^{5} \cdot 3 - делится\ на\ 40.\]
\[3)\ 5 \cdot 2^{962} - 3 \cdot 2^{961} + 2^{960} =\]
\[= 2^{960} \cdot \left( 5 \cdot 2^{2} - 3 \cdot 1 + 1 \right) =\]
\[= 2^{960} \cdot 15 = 2^{958} \cdot 4 \cdot 15 =\]
\[= 2^{958} \cdot 60 - делится\ на\ 60.\ \ \]
\[\boxed{\text{1164.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 4x - y = 7\ \]
\[y = 4x - 7\ \]
\[(0;\ - 7),\ (1;\ - 3).\]
\[2) - 2x + y = 11\ \ \]
\[y = 11 + 2x\text{\ \ }\]
\[(0;11),\ (1;13).\]
\[3)\ 5x - 3y = 15\ \]
\[3y = 5x - 15\ \]
\[y = \frac{5x - 15}{3}\]
\[y = \frac{5}{3}x - 5\ \]
\[(0;\ - 5),\ ( - 3; - 10).\]